Characters and Characterization in Up Movie: Philosophical Value Obtainment - Cut Divyta Harfenia; Fifi Arifida; Nur Fadilah Helda; Sintia Febrianda; Nyak Mutia Ismail (International Conference on Multidisciplinary Research, 2022)
This research aimed at finding out main characters and characterization in a family movie entitled ‘Up’. It is intended to give explanation about the main character namely Carl, Ellie, Russel, and Muntz as portrayed in the movie. The objectives of this research are to identify and analyze these four characters as they are considered the major characters in the movie. During data collection, an arm-chair method consisting of several steps were carried out; they are watching the movie, writing its transcription, reading the transcription, analyzing it, and categorizing the transcription into each relevant character. The data were later analyzed using interactive analysis through data reduction, data display, and data verification. The result shows that there are four characters considered as the major characters in this movie, they are Carl, Ellie, Russel, and Muntz. Carl is a character who gives loyalty value; Ellie depicts companionship value; Russel shows te vlaue of bravery; and Muntz shows a rather antagonistic value, which is greed. In conclusion, this movie is a good object to study as a source of learning, especially for young children and family movies. Keywords: Movie Analysis, Philosophical Values, Protagonists, Antagonists, Characterizations